The Immunological Study of Salmonella Infantis in white Mice Immunized with Killed Antigen - Basimraihan Sahar1, Khalied Yassenzakairalzamily1, Alaa SalimHamzah2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was carried out to investigate the effect of formalin-killed antigen for Sallmonellainfantis in vivo with the study of cellular immune response through the study of cytokines.Sallmonellainfantis were isolated and diagnosed from local milk products (milk and cheese). 74 milk samples and 53 cheese samples were taken.The media were usedgeneral and special culture media as well as biochemical tests were used to diagnose the isolates and the diagnosis was confirmed by using API 20. Sallmonellainfantis antigens were used systemically. 50 Swiss white mice of both sexes were randomly divided into three groups. The first group prevented (20 mice) with the bacterial antigen killed by formalin in a dose (0.3) I.P for each animal. The group was injected with a booster dose and the same first immunization dose two weeks after the first dose. The second group (20 mice) and the third group (10 mice) were counted as positive and negative control groups respectively. The first group and the second group received a dose of 0.3 ml of stuck S.infantis containing (1×108 live cells / ml) I.P, while the third group injected 0.3 ml of neutral phosphate buffer solution under the skin. The results showed that 4 animals from the first group were killed and all the remaining animals from the first group were killed 20 days after the challenge dose and serum was taken to measure cellular immunity. The results of serological tests showed that the level of (IL-4 and IL-6) were (38.48 ± 2.1 and 31.81, 3.01) respectively, as well as the results of measurement of concentration (INF gamma and TNF-?) were (401 ± 2.12 and 173.421 ± 3.11) respectively.We conclude from the study that there was a high percentage of S.infantis isolated from milk products as well as we conclude that the formalinS.infantiskilledantigen partially protected against the infection.